R&D, Human Capital and Export Behavior of Manufacturing and Service Firms in Ghana - Amadu, A.W.; Danquah, M. (Journal of African Business, 2019)
The paper carries out a detailed analysis of the effects of R&D and human capital as well as their interactions with innovation on export behavior of manufacturing and service firms in Ghana using a dataset of 720 firms that merges the Enterprise, Innovative Capability and the Innovation Follow-up Surveys respectively for Ghana. Using a bivariate probit regression, the results show that R&D and human capital (employees’ education, slack time and formal training) are positive and significantly related to the propensity for firms to export in Ghana. The cross derivatives (differences) for the interaction terms (R&D and innovation, and education and innovation) also showed that these interaction terms have positive effects on the likelihood for firms to export but are significant only for a negligibly small fraction of the sample. Thus, there is no much statistically significant evidence in support of the mediation role of innovation in the relationship between R&D/education and the export behavior.
Keywords: R&D; Human capital; Innovation; Export behavior; Firms; Ghana